A profissão docente como prática ilustrada: o caso dos primeiros professores de inglês do Brasil - Santana, Marcle Vanessa Menezes (2013)
The present study has as its objective a biobliographic research of English teachers who contributed to English language teaching in our country in their corresponding institutional contexts. In this sense, we followed the path which led to the construction of the European national ideal, whose underlying assumption was the institution of a national language. In addition, it timidly began during the Enlightenment and was consolidated in the nineteenth century. Moreover, we established the correlation between schooling and the process of teaching professionalization in the eighteenth century, taking into account the Portuguese- Brazilian case, which Pombal s reforms was the basis of laws dispatched during Brazil s empire. Furthermore, we analysed the trajectory of English language in Brazil through the legislation, the selection of the most representative grammars and dictionaries and the role performed by translators and interpreters in the process of affirmation of English language in Brazil. At last, we narrated the professional trajectories of the first English teachers in our country, Eduardo Thomaz Colville, John Joyce and Guilherme Paulo Tillbury, in the condition of Enlightenment intellectuals as well as responsible for the affirmation of that profession as well as English language during the nineteenth century in Brazil.